Versatile approach towards fully desymmetrized trehalose with a novel set of orthogonal protecting groups - Vašíček, Tomáš; Arensmeyer, Benjamin; Monti, Alessandro; Zamyatina, Alla (Frontiers in Chemistry, 2024)
Trehalose-containing glycans play an essental role in bacterial pathogenesis, host-pathogen interaction and cell signaling. The investigation of trehalose uptake and metabolism in Mycobacteria using synthetic desymmetrised trehalose probes is an important approach for the development of diagnostic tools and potential therapeutics for tuberculosis. Trehalose-derived mycobacterial glycolipids activate the innate immune response through recognition by the C-type lectin Mincle, justifying efforts to develop novel trehalose-based Mincle-dependent adjuvants. The chemical synthesis of trehalose-based glycoconjugates, glycolipids and small-molecule trehalose probes requires the challenging chemical desymmetrisation of eight hydroxyl groups in a C2-symmetric disaccharide αGlc(1↔1)αGlc. Using a novel set of orthogonal protecting groups, we developed a flexible multiscale synthetic approach to a collection of differently and variably protected fully desymmetrised trehalose derivatives, ready for final chemical modification with relevant functional or reporter groups. Using a regioselective and sitespecific protecting group strategy, we performed multiple symmetry-breaking operations, resulting in a library of trehalose-derived orthogonally protected building blocks as a versatile source for the synthesis of complex trehalose-containing glycans.